Social Piety Through Community Social-Economic Empowerment At Nurul Ashri Mosque Yogyakarta - Amalia Cahya Rachmayanti (International Journal of Sociology of Religion, 2024)
Mosques have a strategic role as the centre of religious, social, and economic activities of the people. This study aims to analyse the implementation of social piety in the economic and social empowerment of the people at the Nurul Ashri Mosque Yogyakarta. This research uses a qualitative approach with primary data obtained through in-depth interviews, observation, and documentation analysis, as well as secondary data from various related literature and documents. The results showed that the Nurul Ashri Mosque successfully integrated the values of social piety, such as justice, solidarity, and social responsibility, through the management of zakat, infaq, sadaqah, and empowerment programmes. The programmes include skills training, interest-free micro business capital, social assistance distribution, and educational activities. The impact of these programmes includes improving people's standard of living, strengthening social solidarity, and creating economic independence for the congregation. The mosque has also successfully practised the principles of inclusivity and transparency in resource management. With a collaborative approach and community support, the Nurul Ashri Mosque has become a model of sustainable empowerment. This research concludes that the integration of religious values and Islamic philanthropy principles is able to make the mosque a significant agent of social change. Hopefully, this success can be replicated by other mosques to expand the impact of people empowerment in Indonesia.